2022
DOI: 10.1017/s1431927621013994
|View full text |Cite
|
Sign up to set email alerts
|

Status and Direction of Atom Probe Analysis of Frozen Liquids

Abstract: Imaging of liquids and cryogenic biological materials by electron microscopy has been recently enabled by innovative approaches for specimen preparation and the fast development of optimized instruments for cryo-enabled electron microscopy (cryo-EM). Yet, cryo-EM typically lacks advanced analytical capabilities, in particular for light elements. With the development of protocols for frozen wet specimen preparation, atom probe tomography (APT) could advantageously complement insights gained by cryo-EM. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 112 publications
(188 reference statements)
0
6
0
Order By: Relevance
“…As sample material, natural honey from the company Langnese was used. Tungsten wires were used as substrate material and their rough surfaces were produced by applying a tensile force under cryogenic conditions 43 , 44 , 66 . It’s well known that honey has a high viscosity and, therefore, sticks to different surfaces.…”
Section: Experimental Section/methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As sample material, natural honey from the company Langnese was used. Tungsten wires were used as substrate material and their rough surfaces were produced by applying a tensile force under cryogenic conditions 43 , 44 , 66 . It’s well known that honey has a high viscosity and, therefore, sticks to different surfaces.…”
Section: Experimental Section/methodsmentioning
confidence: 99%
“…9 B. This method cannot be used for low viscous liquids; therefore, a dedicated method was developed as reported in 43 , 44 , 66 . After that, the sample holder was transferred as fast as possible into the body of the cooled transfer shuttle VCT500 from Leica (T = − 184 °C).…”
Section: Experimental Section/methodsmentioning
confidence: 99%
“…Our preceding demonstrator experiments have indeed shown that APT analysis of water is possible. [ 40 , 41 ] We make the surprising observations that the reaction product is not formed (and removed) as a film on the reaction surface but stored in nanoscale dispersed form at the inner reaction regions and trapped as nanoscale water‐metal inclusions inside the reduced iron.…”
Section: Introductionmentioning
confidence: 99%
“…The particular goal of this study is to investigate whether the size of the evaporated fragments can be influenced by variation of the laser energy. Biological and organic materials are on the rise in the atom probe community and thanks to the developments of FIB cryo-preparation techniques (Gerstl & Wepf, 2015; Gerstl et al, 2017; Cairney et al, 2019; El-Zoka et al, 2020; Schwarz et al, 2020; Chen et al, 2021; Stender et al, 2021), even room temperature liquids are becoming accessible. In view of the typically obtained complex mass spectra with many different molecular fragments, even from simple hydrocarbon systems, it is crucial to understand which conditions yield which kind of molecular ions.…”
Section: Introductionmentioning
confidence: 99%